The Reduction of Greenhouse Gas Emissions and Energy Optimization in Apricot Production in Turkey - Hayran, Seyit; Donmez, Rifki; Karabacak, Tuba; Kulekci, Murat (Springer, 2023)
The aim of this study is to optimize energy consumption and reduce greenhouse gas (GHG) emissions in apricot production in Turkey, which has the highest share in apricot production in the world. A data envelopment analysis (DEA) approach was used to distinguish efficient and inefficient farms, based on data collected from 108 apricot farms through face-to-face surveys, in order to determine the optimum level of energy usage. Thus, the amount of GHG emissions and input energy to be saved by using the optimum energy input were determined. The results revealed that the total, pure and scale efficiencies of apricot producing farms were on average 0.797, 0.904 and 0.875, respectively. The rate of energy saving has been determined as 21.78%. This means that the current apricot production amount can be produced using 5349.12 MJ ha(-1) less input energy. The highest contribution to total energy savings is made by farmyard manure with 35.24%, followed by irrigation and fertilizer with 32.82%, respectively. In this study, it was determined that the amount of GHG emissions released into the environment from apricot production can be reduced by 19.50% with energy optimization.
Keywords: Apricot; Energy use; Technical efficiency; Scale efficiency; GHG emissions